Dynamic analysis model of a class E2 converter for low power wireless charging links. Issue 3 (1st April 2019) - Bati, Akram; Luk, Patrick C.K.; Aldhaher, Samer; See, Chan H.; Abd‐Alhameed, Raed A.; Excell, Peter S.
Abstract : A dynamic response analysis model of a Class E 2 converter for wireless power transfer applications is presented. The converter operates at 200 kHz and consists of an induction link with its primary coil driven by a class E inverter and the secondary coil with a voltage‐driven class E synchronous rectifier. A seventh‐order linear time invariant state‐space model is used to obtain the eigenvalues of the system for the four modes resulting from the operation of the converter switches. A participation factor for the four modes is used to find the actual operating point dominant poles for the system response. A dynamic analysis is carried out to investigate the effect of changing the separation distance between the two coils, based on converter performance and the changes required of some circuit parameters to achieve optimum efficiency and stability. The results show good performance in terms of efficiency (90–98%) and maintenance of constant output voltage with dynamic change of capacitance in the inverter. An experiment with coils of the dimension of 53 × 43 × 6 mm 3 operating at a resonance frequency of 200 kHz, was created to verify the proposed mathematical model and both were found to be in excellent agreement.